(untitled) (International Journal of Environmental Sciences, 2025)
Background: Adolescence is an important and sensitive phase of life. Due to restrictions and negative attitude of parents in discussing menstruation-related issues with girls has led to poor awareness regarding menstruation and menstrual hygiene among adolescent girls. The present study was proposed to be carried out to find out their knowledge about menstrual pattern and menstrual hygiene practice. Material and Methods: The present study was school-based educational interventional study conducted at the Department of Obstetrics and Gynaecology in MIMER Medical College and Dr. BSTR Hospital in Talegaon (D), Pune. The study was conducted from March 2018 to May 2018. The study population was all adolescent school girls of age group 15-18 years and given consent were registered for inclusion in the study. Permission from the Ethical Committee was taken prior to commencement of the study and informed written consent was taken from the participants of the study. Pre designed, pre tested, semi structured questionnaire was used to collect the information from the study participants. Data was entered into a unified computer database and analysed. The statistical analysis was done using SPSS 24.0. Results: Among the 100 study participants, nearly half (48%) were aged between 15–16 years, followed by 34% in the 16–17 age group. The majority experienced menarche between the ages of 12–14 years (58%). The majority of subjects were from lower Socioeconomic class (48%) Post-test results showed improvement in knowledge understanding topics like pad usage, hygiene practices (genital and hand washing), bathing during menstruation, and the role of nutrition and exercise. Awareness of common menstrual problems and puberty changes also increased significantly to 78% and 82%, respectively with statistically significance. (P<0.001) Conclusion: There was a significant improvement in the level of good and satisfactory knowledge and practice about menstruation following health education intervention.